Kompetanseutvikling i et profesjonelt læringsfellesskap: En studie av læreres samtaler om undervisning for dybdelæring - Majken Korsager; Berit Reitan; Maria Gaare Dahl (Nordina: Nordic Studies in Science Education, 2023)
A way to facilitate schools in adapting to a changing society, is through teachers’ professional development in learning communities. This study followed a group of primary school teachers in a professional learning community at their own school, as they discussed principles of teaching for deep learning while working with a resource for professional development in science education. The purpose of the study has been to explore if and how conducting the resource in their local learning community would contribute to the teachers’ professional development in teaching for deep learning. The results indicates changes in the teachers’ perspectives during the process, from emphasizing challenges to emphasizing strengths and possibilities associated to implementing principles for deep learning in their teaching. The changes of perspectives appears to relate to how the teachers’ self-efficacy was influenced positively by the students’ response as they implemented the principles in their teaching practice.